Determination of atmospheric aerosol components in an urban area to evaluate the air quality and identify the sources of contamination - Bedregal, Patricia (2023)
The need to generate objective evidence and reliable information for decision makers to improve environmental policies for a better air quality, led us to evaluate the atmospheric aerosol components in the urban area of Carabayllo, by monitoring PM2.5 and PM10 to determine mass concentration and analyzing PM10 using k0-INAA and ICP–MS for metals quantification, ion chromatography for anions and the NIOSH method to determine organic and elemental carbon. The results obtained from mass concentration of PM2.5 and PM10 exceeded the permissible breathing annual average of WHO guidelines of 15 µgm−3 and 45 µgm−3, respectively, which evidence an unhealthy air quality. Likewise, using the model Positive Matrix Factorization five sources of pollutants were defined: metallurgical industry, sea salt, industrial activity, dust and non-exhaust emissions and vehicle emissions.